2016
DOI: 10.1111/1462-2920.13402
|View full text |Cite
|
Sign up to set email alerts
|

Species‐sorting and mass‐transfer paradigms control managed natural metacommunities

Abstract: A complex microbial system consisting of six different interconnected localities was thoroughly investigated at full scale for over a year. The metacommunity concept originating from macro-ecology was used to uncover mechanisms of community assembly by observing microbial interrelationships in and between the different localities via correlation and network analysis. The individual-based observation approach was applied using high-throughput microbial community cytometry in addition to next generation sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 60 publications
1
44
0
Order By: Relevance
“…Therefore, testing for the strength of interconnections between microorganisms and their environment may reveal situations in which niche differentiation is or is not fulfilled. Recent studies have confirmed that the number of correlations between subcommunities and abiotic parameters can unravel these interconnections (Faust and Raes, ; Günther et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, testing for the strength of interconnections between microorganisms and their environment may reveal situations in which niche differentiation is or is not fulfilled. Recent studies have confirmed that the number of correlations between subcommunities and abiotic parameters can unravel these interconnections (Faust and Raes, ; Günther et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Second, niche differentiating mechanisms were disclosed by the numbers of detected significant correlations. An increased number of positive or negative correlations suggest both increasing interactions between organisms and between organisms and abiotic parameters (Seebacher and Franklin, 2012;Faust and Raes, 2012;Needham and Fuhrman, 2016;Günther et al, 2016). Adaptations to new conditions are known to cause not only changes in cell states, e.g.…”
Section: The Relative Roles Of Niche Differentiation Vs Neutral Mechmentioning
confidence: 99%
“…Within 2 h after sampling time, the process of drying homogenized wastewater was initiated, and the remaining wastewater was stored at 4°C. (Günther et al, 2016 Remaining wastewater was also homogenized before it was added to the drying setup. Wastewater samples used for the analysis provided by Günther et al (2016) (Table 1) were sampled at the same time.…”
Section: Sampling and Storage Of Wastewatermentioning
confidence: 99%
“…(Günther et al, 2016 Remaining wastewater was also homogenized before it was added to the drying setup. Wastewater samples used for the analysis provided by Günther et al (2016) (Table 1) were sampled at the same time. 50 mL of 20 samples (January 2014-July 2014) were stored at −20°C for further experiments (dry weight).…”
Section: Sampling and Storage Of Wastewatermentioning
confidence: 99%
See 1 more Smart Citation